Immune response and prevalence of antibody to Norwalk enteritis virus as determined by radioimmunoassay. - Blacklow, N R (1979)
A solid-phase microtiter radioimmunoassay was established for the detection of Norwalk virus and its antibody, with clinical materials from human volunteers previously studied in Massachusetts as reagents. A study of 308 Massachusetts residents showed that serum antibody to Norwalk agent was rarely present during childhood but was detectable in approximately 50% of adults. All volunteers inoculated with Norwalk virus who developed illness seroconverted (10/10), whereas only one-third (5/15) of nonill volunteers seroconverted (P = 0.0009). The 10 nonill, nonseroconverting subjects had undetectable to low preexisting antibody levels. Paradoxically, 10/13 subjects with preexisting antibody became ill, whereas 17/25 lacking antibody did not (P = 0.009). All 3 subjects with preexisting anti-Norwalk radioimmunoassay blocking activity in duodenal intraluminal fluids became ill, whereas only 5/11 lacking such activity developed illness (P = 0.15). These data further support the unique concept that some individuals are susceptible to repeated infections with this agent, whereas others are incapable of developing infection.